2022
DOI: 10.1155/2022/3424972
|View full text |Cite|
|
Sign up to set email alerts
|

A Meta-Analysis to Detect Efficacy of Physical Activity Interventions to Enhance Effects Related to the Fragility among Older Adults

Abstract: Background. The role of physical activity is well-known to intercept the condition of fragility and decrease its outcomes. This study aimed to determine the efficacious physical activity intervention measure which enhances the outcomes associated to fragility in the older adults. Material and Methods. We searched MEDLINE, Cochrane Central Register of Controlled, and EMBASE for the published studies in the duration June 2000 to February 2020 which were further shortlisted as per the inclusion and exclusion crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…The study that used a more comprehensive indicator, incorporating financial status as one of its many components, namely socioeconomic status (SES), showed that a better socioeconomic status linked positively to the 'pro-healthy eating and more-active' pattern [49]. This is corroborated by previous studies that showed the positive impact of a higher socioeconomic status on attitudes toward healthy dietary patterns [56], dietary behaviors [57,58], dietary patterns [59], and nutritional status [60], as well as greater physical activity [61] in older adults. However, it should be noted that higher SES was associated with lower sleep duration [62] in older adults.…”
Section: Discussionsupporting
confidence: 64%
“…The study that used a more comprehensive indicator, incorporating financial status as one of its many components, namely socioeconomic status (SES), showed that a better socioeconomic status linked positively to the 'pro-healthy eating and more-active' pattern [49]. This is corroborated by previous studies that showed the positive impact of a higher socioeconomic status on attitudes toward healthy dietary patterns [56], dietary behaviors [57,58], dietary patterns [59], and nutritional status [60], as well as greater physical activity [61] in older adults. However, it should be noted that higher SES was associated with lower sleep duration [62] in older adults.…”
Section: Discussionsupporting
confidence: 64%
“…Some systematic reviews have been published that evaluate the effect of physical exercise programs to improve functional capacity in older adults at the community level, in which it is reported that exercise program training has a positive effect on physical performance in healthy older adults and improves the function of those who are frail [10,11]. However, these studies do not compare the results regarding the effect on older adults without or with frailty.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are barriers related to the environment [16], such as transportation problems [17] and places with reduced accessibility [12], which in turn generate the fear of falling [10]. All these barriers contribute to a sedentary lifestyle, which in turn can accelerate the onset of diseases [18], and consequently increase the chances that individuals will become fragile and vulnerable to a series of life circumstances [19], consequently affecting their autonomy and adaptation to the environment [20].…”
Section: Introductionmentioning
confidence: 99%